Cost-effectiveness of the sFlt-1/PlGF ratio test in pregnant patients with suspected pre-eclampsia: a systematic reviewAJOG Global Reports at a Glance - Charlotte S. Goutallier, MD; Alayna Carrandi, MPH; Shaun P. Brennecke, MBBS, DPhil; Emily J. Callander, PhD (AJOG Global Reports)
Objectives: Pre-eclampsia (PE) affects approximately 2%–4% of pregnancies. Diagnosis involves repeated assessment of pregnant patients with risk factors. The sFlt-1/PlGF ratio test is shown to have clinical utility in ruling in and out PE among at-risk patients. By excluding the probability of PE, the addition of the sFlt-1/PlGF ratio test to antenatal care may prevent unnecessary hospital admissions, intensive management, and premature delivery, thus reducing costs. The objective of this systematic review is to determine the cost-effectiveness of the sFlt-1/PlGF ratio test globally for pregnant patients at-risk of developing PE. Data sources: PubMed, Medline (OVID), National Health Service Economic Evaluation Database, Web of Science, Econlit, and Cost Effectiveness Analysis Registry was systematically searched between 2013-April 2023. Study eligibility criteria: Empirical studies quantifying costs of the sFlt-1/PlGF ratio test compared to other diagnostic options for pregnant patients with suspected PE. Study appraisal and synthesis methods: Eleven studies were included in the systematic review; all were cost analyses and modelled economic evaluations, and most used a health system perspective. Cost data were extracted into tables and indexed to 2022 United States Dollars (USD). An assessment of risk of bias for each study was performed using the Drummond critical appraisal checklist. Results: All studies reported “cost-savings” of the test in antenatal care. Studies varied with costs and assumptions included, therefore a large range of incremental cost savings per patient was reported ($15–$1,881, 2022USD). No Incremental Cost-Effectiveness Ratios or health outcomes including Quality Adjusted Life Years were reported. Conclusions: The included studies demonstrated “cost-savings” of the sFlt-1/PlGF ratio test in antenatal care for at-risk pregnant patients. However, this does not account for health outcome differences and long-term health care utilisation and expenditure.